Quantification of eucalyptol (1, 8‐cineole) in rat serum by gas chromatography–mass/mass spectrometry and its application to a rat pharmacokinetic study. (9th February 2021) - Sa, Chula; Liu, Jinlei; Dong, Yu; Jiang, Li; Gentana, Ge; Wurita, Amin
Abstract: Eucalyptol (1, 8‐cineole) is a biologically active cyclic monoterpenoid. In a preliminary study, we used gas chromatography–mass spectrometry to detect eucalyptol in the serum and brain tissue of rats after oral administration. However, the absorption characteristics in vivo and pharmacokinetic parameters of eucalyptol have not been published to date. The present study aims to develop and validate a simple, sensitive GC–MS/MS method with quadrupole mass analyzer type for the quantitative analysis of eucalyptol in rat serum and apply it to a pharmacokinetic study. The assay showed linearity of concentration range from 50 to 5, 000 pg/ml with a limit of quantitation of 50 pg/ml. Intra‐ and inter‐day precision for eucalyptol were 4.4–13.0 and <15.0%, respectively, and accuracy was within 10% for quality control samples. The recovery and stability results showed that the method was accurate and stable for quantitative analysis. The developed analytical method was successfully applied to a pharmacokinetic study after a single oral administration of eucalyptol in rat subjects. The serum concentration–time profiles indicate that the absorption characteristics of eucalyptol after oral administration are similar to those for intravenous administration.